No relationship between 2',3'-cyclic nucleotide 3'-phosphodiesterase and schizophrenia in the Chinese Han population: an expression study and meta-analysis - Zhang Zhao; Wei Zhiyun; Zhang Jing; Tang Wei; Che Ronglin; Huang Ke; Zhao Xinzhi; Gao Jianjun; Zhou Guoquan; Huang Peirong; He Lin; Shi Yongyong (BMC, 2009)
Abstract Background 2',3'-Cyclic nucleotide 3'-phosphodiesterase (CNP), one of the promising candidate genes for schizophrenia, plays a key part in the oligodendrocyte function and in myelination. The present study aims to investigate the relationship between CNP and schizophrenia in the Chinese population and the effect of different factors on the expression level of CNP in schizophrenia. Methods Five CNP single nucleotide polymorphisms (SNPs) were investigated in a Chinese Han schizophrenia case-control sample set (n = 180) using direct sequencing. The results were included in the following meta-analysis. Quantitative real-time polymerase chain reaction (PCR) was conducted to examine CNP expression levels in peripheral blood lymphocytes. Results Factors including gender, genotype, sub-diagnosis and antipsychotics-treatment were found not to contribute to the expression regulation of the CNP gene in schizophrenia. Our meta-analysis produced similar negative results. Conclusion The results suggest that the CNP gene may not be involved in the etiology and pathology of schizophrenia in the Chinese population.